Frequency of thyroid dysfunctions during interferon alpha treatment of single and combination therapy in hepatitis C virus-infected patients: a systematic review based analysis. - Chandrasekharan Nair Kesavachandran; Frank Haamann; Albert Nienhaus (PLoS ONE)
Background Thyroid dysfunction is the commonest endocrinopathy associated with HCV infection due to interferon-based treatment. This comprehensive and systematic review presents the available evidence for newly developed thyroid antibodies and dysfunctions during interferon treatment (both single and combination) in HCV patients. Methodology/principal findings This systematic review was conducted in accordance with the PRISMA guidelines. The data generated were used to analyze the risk for thyroid dysfunctions during interferon (IFN) treatment in HCV patients. There was a wide range in the incidence of newly developed thyroid dysfunctions and thyroid antibodies in HCV patients during IFN treatment (both single and combination). The wide range of incidence also denoted the possibility of factors other than IFN treatment for thyroid-related abnormalities in HCV patients. These other factors include HCV viral factors, genetic predisposition, environmental factors, and patho-physiological factors. Variations in IFN dosage, treatment duration of IFN, definition/criteria followed in each study for thyroid dysfunction and irregular thyroid function testing during treatment in different studies influence the outcome of the single studies and jeopardise the validity of a pooled risk estimate of side effects of thyroid dysfunction. Importantly, reports differ as to whether the thyroid-related side effects disappear totally after withdrawal of the IFN treatment. Conclusions/significance The present review shows that there is a wide range in the incidence of newly developed thyroid dysfunctions and thyroid antibodies in IFN treated HCV patients. This is a comprehensive attempt to collate relevant data from 56 publications across several nations about IFN (both mono and combination therapy) related thyroid dysfunction among HCV patients. The role of each factor in causing thyroid dysfunctions in HCV patients treated with IFN should be analyzed in detail in future studies, for a better understanding of the problem and sounder clinical management of the disease.